Acrylic denture base repair (Part III): In-fluence of repair procedure on color and residual monomer - Nadira A Hatim; Mohammed M Sadoon (University of Mosul, College of Dentistry, 2006)
Aims: To evaluate the effect of repair techniques, surface treatment with monomer, and additional curing cycle on the color change, and residual monomer of the repaired denture base. Materials and methods: Two hundred and seventy two samples of two brands heat cured acrylic resin were repaired by four different techniques (water bath, microwave, thermo press, and chemically cured acrylic resin), treated, and untreated with monomer, and repaired with 3 mm space at fracture area. The samples were tested to measure color change and residual monomer of repaired, and intact (control) samples. Results: Color change of acrylic denture base repaired by chemically cured acrylic resin was significantly higher than that of water bath, microwave, and thermo press. Microwave repairing technique had lower residual monomer than other techniques. The highest content of residual monomer was released in water after the first 24 hours and decreased in the subsequent days. Acrylic denture base that has additional curing cycle showed a residual monomer content lower than those with single curing cycle. Conclusion: Color changes of repaired denture with chemically cured resin are high and the lower adverse effect of monomer are shown with microwave and water bath curing cycle. Long storage period of repaired denture base are beneficial to reduce monomer release